2017
DOI: 10.1242/jcs.198903
|View full text |Cite
|
Sign up to set email alerts
|

The ShcD phosphotyrosine adaptor subverts canonical EGF receptor trafficking

Abstract: Shc family signalling adaptors connect activated transmembrane receptors to proximal effectors, and most also contain a sequence involved in clathrin-mediated receptor endocytosis. Notably, this AP2 adaptin-binding motif (AD) is absent from the ShcD (also known as Shc4) homolog, which also uniquely promotes ligand-independent phosphorylation of the epidermal growth factor receptor (EGFR). We now report that cultured cells expressing ShcD exhibit reduced EGF uptake, commensurate with a decrease in EGFR surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…For example, recently published work has shown that SHCD overexpression results in a significant increase in phosphorylation of EGFR in a PTB-dependent manner. The largest increases occurred at the SHCD PTB-binding site, pTyr-1148, and to a lesser extent at pTyr-1068 and pTyr-1173 (37). These data are highly consistent with phosphosite protection, although this was not considered as a potential mechanism.…”
Section: Analysis Of In Vivo Ptyr Protection By Sh2 Domainssupporting
confidence: 58%
See 1 more Smart Citation
“…For example, recently published work has shown that SHCD overexpression results in a significant increase in phosphorylation of EGFR in a PTB-dependent manner. The largest increases occurred at the SHCD PTB-binding site, pTyr-1148, and to a lesser extent at pTyr-1068 and pTyr-1173 (37). These data are highly consistent with phosphosite protection, although this was not considered as a potential mechanism.…”
Section: Analysis Of In Vivo Ptyr Protection By Sh2 Domainssupporting
confidence: 58%
“…GRB2 mediates signaling through a complex series of downstream pathways that could indirectly enhance EGFR phosphorylation, for example by increasing cytoplasmic kinase activity or suppressing phosphatase activity (35)(36)(37). To rule out downstream signaling as a driver of GRB2-mediated EGFR phosphoenhancement, we compared protein tyrosine phosphorylation after expression of full-length WT GRB2 and four GRB2-derived constructs as follows: a fluorescently tagged GRB2 SH2 domain (tdEOS-GRB2 SH2), previously shown to be recruited to the plasma membrane of EGF-stimulated cells (34,38); fulllength GRB2 and tdEOS-GRB2 SH2 constructs containing a mutation in the SH2 domain (R86K) previously shown to abrogate phospho-dependent interaction (39,40); and a chimeric protein in which the SH2 domain of GRB2 is replaced by that from CRK, referred to here as GCG ( Fig.…”
Section: Grb2 Sh2 Domain Overexpression Enhances Egfr Phosphorylationmentioning
confidence: 99%
“…SHC4 is one of the proteins of the Src homology and collagen family, ShcA, ShcB, ShcC and SHC4 (or ShcD), in chronological order of their discovery. Shc proteins are known to engage in the EGFR internalization process 25 , and ShcD was reported to alter steady-state EGFR trafficking dynamics, which reduces cellular ligand sensitivity by recruiting the EGFR into juxtanuclear vesicles identified as Rab-11-positive endocytic recycling compartments 26 .…”
Section: Discussionmentioning
confidence: 99%
“…GDNF treatment was previously shown to provoke RET internalization [23] , which indeed supports the endosomal colocalization of ShcD and RET in GDNF-treated cells. Ina addition, a recent report by Will and et al showed that ShcD colocalizes with EGFR at the perinuclear endosomal compartment [24] .…”
Section: Discussionmentioning
confidence: 95%